All‐carbon N‐heterocyclic Carbene‐catalyzed (3+2) Annulation using Donor‐Acceptor Cyclopropanes. Issue 6 (25th February 2016) - Candish, Lisa; Gillard, Rachel M.; Fernando, Jared E. M.; Levens, Alison; Lupton, David W.
Abstract: Donor‐acceptor cyclopropanes are known to serve as dipole precursors capable of engaging in (3+2) annulations with electron‐deficient π‐systems. In 2013, the reaction of donor‐acceptor cyclopropanes with α, β‐unsaturated acyl fluorides in an all‐carbon (3+2) annulation was discovered. The reaction proceeds in good yields using the IMes NHC to provide diastereomerically pure β‐lactone‐fused cyclopentanes bearing four contiguous stereocentres. Subsequent studies demonstrated that N‐ t‐ butyl substituted homochiral morpholinone NHCs allowed the reaction to be achieved in up to 98 % ee . In this account, a background to this reaction is introduced, along with a complete account of the strengths, limitations and challenges encountered while developing this chemistry. Abstract :